POTENTIAL FOR MOSQUE-BASED COMMUNICATION CONFLICT IN ACEH - Juhari; Zulfadli (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
In Islamic literature, a mosque is generally understood as a sacred place used for gathering and worship. It is both a place of worship and a unifying medium for Muslims. There are no restrictions on any Muslim, regardless of ethnicity or race, from gathering and carrying out activities in a mosque—except those stipulated in Islamic law. Therefore, the mosque truly serves as a unifying symbol of the Islamic community across all regions and areas. Aceh is one of the regions with a large number of mosques. However, behind the abundance of mosques in Aceh, there are also potential conflicts within them, which can create space for the division of society into certain groups. The investigation into this potential conflict was conducted through a qualitative research approach. Data collection was conducted in 10 regencies/cities, starting from the provincial capital. Then, the data was relayed to three zones: representing the east coast, the west coast, and the central zone. The research results indicate several potential miscommunications that could lead to mosque-based conflicts. This is also triggered by several factors, including not all members of the community fully understanding Islamic teachings and the arrogance of religious elites in communicating differences, which has given rise to sectoral conflicts. Likewise, communication between elites/rulers is less than wise with mosque administrators, giving rise to vertical conflict, and there is less than transparent behavior from mosque administrators, giving rise to horizontal conflict.